Spillover Effects of Maternal Education on Child's Health and Schooling - Daniel Kemptner; Jan Marcus (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This is the first study investigating the causal effect of maternal education on child's health and schooling outcomes in Germany. We apply an instrumental variables approach that has not yet been used in the intergenerational context. For that purpose, we draw on a rich German panel data set (SOEP) containing information about three generations. This allows instrumenting maternal education by the number of her siblings while conditioning on a set of variables describing the grandparents' social status and the area where the mother grew up. Given these variables, the number of siblings generates exogenous variation in the years of education by affecting the household resources available per child. We present evidence for strong and significant effects on schooling outcomes for both sexes. And, we find substantial effects on health behaviour for adolescent daughters, but not for adolescent sons. We show that possible concerns for the validity of the instrument are unlikely to compromise these results. We also discuss assortative mating and household income as possible channels of causality.
Keywords: C26; I12; I21; J62; 330; Intergenerational mobility; returns to education; health; instrumental variables; Mütter; Bildungsniveau; Spillover-Effekt; Kinder; Bildungsabschluss; Gesundheit; Panel; Sozialforschung; Deutschland